2019
DOI: 10.1107/s2052520619014380
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of triclinic and monoclinic SFCA-III – killing two birds with one stone

Abstract: Synthesis experiments in the system CaO–SiO2–Al2O3–Fe2O3–MgO resulting in the formation of SFCA-III are reported. SFCA-III is a new n = 2 member of a polysomatic series of M 14+6nO20+8n compounds based on pyroxene-spinel modules which are of relevance to iron-ore sintering. Single-crystal diffraction studies using synchrotron radiation revealed that the compound occurs in two polytypes representing maximum degree of order structures which explains the observed allotwinning of the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…X 21,22) and SFCA-II [23][24][25] are crystallographically closely related. It has also been shown that the alumina-free silico ferrite of calcium (SFC) phase has a crystal structure identical to the SFCA phase.…”
Section: Sfca Nucleationmentioning
confidence: 99%
“…X 21,22) and SFCA-II [23][24][25] are crystallographically closely related. It has also been shown that the alumina-free silico ferrite of calcium (SFC) phase has a crystal structure identical to the SFCA phase.…”
Section: Sfca Nucleationmentioning
confidence: 99%
“…2a). This modular approach has been already outlined in detail using concepts of ODtheory in several previous publications for the different members of the SFCA family (Merlino & Zvyagin, 1998;Zvyagin & Merlino 2003;Kahlenberg et al 2019). As can be seen from Fig.…”
Section: Crystal Structurementioning
confidence: 99%
“…Their complex crystal structures exhibit low triclinic symmetry, comparatively large unit-cell volumes, and there is a clear structural relationship between them. Indeed, SFCA and SFCA-I belong to a so-called polysomatic series with general composition A 14+6n O 20+8n (A: Ca, Al, Mg, Si, Fe 3+ , Fe 2+ ) where they represent the members with n = 0 and 1, respectively (see Kahlenberg et al 2019 and references cited therein). The crystal structures of the series allow for a couple of cation substitution mechanisms, which can be summarized according to the following exchange reaction: 2(Fe 3+ ,Al 3+ ) = (Ca 2+ ,Fe 2+ ) + Si 4+ (Patrick and Lovel 2001;Patrick and Pownceby 2002).…”
Section: Introductionmentioning
confidence: 99%
“…3). This modular approach has been already outlined in detail in several previous publications for other members of the SFCA-family (see Kahlenberg et al 2019 and references cited therein). Therefore, we will restrict our description to the key point of this concept.…”
Section: Crystal Structurementioning
confidence: 99%